(untitled) (International journal of artificial intelligence, 2026)
this article is devoted to the methodology for the formation of vocational guidance skills in future educators. The article discusses the pedagogical importance of vocational guidance, the importance of guiding students correctly in choosing a profession through the use of methodological approaches, practical training, psychological approach and modern technologies that should be carried out by future educators. The role of the educator in giving motivation and the importance of fighting stereotypes is also emphasized in vocational guidance. The article is aimed at developing effective methods of vocational guidance in the pedagogical system.